A Breakthrough in Learning and Teaching Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, a new program for teaching foreign languages is introduced to the public. Through the method presented in this program, how to achieve reliable and perfect mastery of the English language in a short period of time will be explained theoretically and practically. An aspect that increases the prestige of the program is that all research and examples of the new method are interpreted in the school English textbooks selected on the basis of state standards: "Guess What?" (grades 1-6) and "Prepare" (grades 7-11). This shows that with this method, students become English language specialists right at the school level.